On the shell thickness-stretching effects using seven-parameter triangular element - Rezaiee-Pajand, M.; Masoodi, Amir R.; Arabi, E. (European Journal of Computational Mechanics, 2018)
In this study, two triangular shell element having three and six nodes are presented for geometrically nonlinear analysis of thin and thick shell structures. The main contribution of this research is to achieve efficient seven-parameter shell elements, which can be employed in the geometrically nonlinear analysis of thin, moderately thick and thick shell structures. The present formulation employs seven degrees of freedom at each node of elements. Owing to this fact, thickness variation is considered as degree of freedom. This formulation makes it possible to investigate the effect of thickness-stretching and calculate its value for all types of shells, especially thick ones. To avoid shear and membrane locking, the Mixed Interpolation of Tensorial Components (MITC) is adopted in formulation. In addition, the fully 3D constitutive relation is used due to consideration of the thickness variation. Furthermore, several nonlinear benchmark problems are studied to illustrate the accuracy and ability of authors’ scheme in comparison with that of other references. Consequently, the effects of thickness extension on the results will be investigated in most of them by presenting the related equilibrium paths of shells with different values of thickness.